Alternative splicing in the human gene for the core protein A1 generates another hnRNP protein. - Buvoli, M (1990)
The human hnRNP core protein A1 (34 kd) is encoded by a 4.6 kb gene split into 10 exons. Here we show that the A1 gene can be differentially spliced by the addition of an extra exon. The new transcript encodes a minor protein of the hnRNP complex, here defined A1B protein, with a calculated mol. wt of 38 kd, that coincides with a protein previously designated as B2 by some authors. In vitro translation of the mRNAs selected by hybridization with A1 cDNA produced two proteins of 34 and 38 kd; Northern blot analysis of poly(A)+ RNA from HeLa cells revealed that the abundance of the A1B mRNA was approximately 5% that of A1. The A1B protein was detected by Western blotting with an anti-A1 monoclonal antibody both in enriched preparations of basic hnRNP proteins and in 40S hnRNP particles. The A1B protein exhibits a significantly higher affinity than A1 for ssDNA. The recombinant A1B protein, expressed in Escherichia coli, shows the same electrophoretic mobility and charge as the cellular one.